Fabrication, phase and microstructural studies on chemically modified La-doped bismuth sodium titanate ceramics - P. Eaksuwanchai (2018)
In this research, heavily-doped (Bi0.5Na0.5)1-1.5xLaxTiO3ceramics with La up to x = 0.2 were prepared by a solid state reaction with chemical modification. The powders were prepared by calcining at 800°C for 2 h and ceramic pellets were fabricated by sintering at 1050 - 1200°C for 2 h under ambient atmosphere. Phase, microstructure, dielectric and ferroelectric properties were investigated. It was found that nearly single phase of chemically modified La-doped BNT ceramics was obtained with much less secondary phase compared to conventional La-doped BNT ceramics. SEM micrographs showed that the grain size increased with La concentration and this trend was opposite to that of unmodified ceramics. Dielectric and ferroelectric properties were also found to be improved in modified ceramics due to the absence of secondary phase and enlarged grain size. © 2013 Copyright Taylor and Francis Group, LLC.